Dimensions of Audit Committee Quality and CEO Compensation: Examining the Linear Relationship - Okolo, Marvis Ndu; Sinebe, Michael Tonbraladoh (International Journal of Economics and Financial Issues, 2024)
This study examined the linear relationship between audit committee attributes, proxied with audit committee female diversity, audit committee diligent meeting, audit committee independence and audit committee size and Chief Executive Officer’s compensation, with firm size as a control variable. The study utilised data from 53 non-financial firms between 2013 and 2022 listed in the Nigerian Exchange Group. Using, STAT 14, the study also presented the descriptive statistics information, the correlation matrix and results of Random-effects GLS regression of the study. The results indicate that approximately 6.88% of the variation in Chief Executive Officer’s compensation can be explained by the combined effect of the independent variables, as evidenced by an R-squared value of 0.0688 and an adjusted R-squared of 0.0599. The model’s overall significance is confirmed by an F-statistic of 7.75 and a very low P-value (0.0000), we therefore reject the null hypothesis. The findings reveal that audit committee female diversity, audit committee diligent meeting, and audit committee independence do not have significant linear relationships with CEO compensation, as indicated by their respective P-values (0.542, 0.814, and 0.916). However, audit committee size displays a statistically significant negative linear relationship with CEO compensation (P = 0.000), suggesting that larger audit committees may be associated with lower CEO compensation due to increased oversight or stronger corporate governance structures. Consequently, further investigation with additional variables or alternative modelling approaches is recommended to gain deeper insights into other determinants of CEO compensation.